The Impact of Entrepreneurial Motivation, Competency, and Orientation on Garlic Farming Performance in Sembalun District - Hasanah, Shabilla Uswatun; Lestari Rahayu Waluyati; Any Suryantini (Jurnal Manajemen dan Agribisnis, 2024)
Sembalun District is the center of garlic farming in East Lombok Regency and one of the areas with the highest garlic production in Indonesia. Garlic is a commodity with very high demand in Indonesia and continues to increase. However, this demand is primarily supported by imports. On the other hand, garlic farming has high risks due to dependence on the weather. Therefore, farmers must have good entrepreneurial skills to optimize the performance of their farming business. This research aims to determine the influence of entrepreneurial motivation, entrepreneurial competency, and entrepreneurial orientation on the business performance of garlic farmers in Sembalun District. The research uses primary data taken from 70 garlic farmers spread across five villages in Sembalun District. The analytical method used in this research is SEM PLS analysis with the help of SmartPLS software version 4.0. The research results show that (1a) pull motivation has a positive effect on entrepreneurial orientation; (1b) push motivation has a negative effect on entrepreneurial orientation; (1c) entrepreneurial competency has a positive impact on entrepreneurial orientation; (2a) pull motivation has a positive effect on farming business performance; (2b) push motivation has a negative effect on farming business performance; (2c) entrepreneurial competency has no impact on farming business performance; (3) entrepreneurial orientation has a positive effect on farming business performance. Keywords: entrepreneurial motivation, entrepreneurial competency, entrepreneurial orientation, farming performance, garlic